Adaptation of the International Standards for Anthropometric Assessment for Subjects With Motor Disabilities: A Consensus Statement of the ISAK Working Group on Motor Disability. - Broad, Elizabeth M.; Cunha, Carlota L.; Caraveo, Luz A.; Acosta, Eder A.; Martín-Almena, Francisco J.; Vieira, Filomena S. (International Journal of Sport Nutrition & Exercise Metabolism, 2026)
The International Standards for Anthropometric Assessment (International Society for the Advancement of Kinanthropometry [ISAK]) have been developed and refined over a period of over 30 years in order to guide the landmarking and measurement of a wide range of surface anthropometrical variables in able-bodied individuals in order for such measures to be reliable, repeatable, and valid. While numerous researchers and practitioners have undertaken anthropometrical assessments on individuals with motor disability, there is a lack of consistency in the processes used, and the ISAK protocol currently does not guide adaptations for measurement or interpretation in this population. Therefore, the ISAK working group on motor disability has reviewed the literature and provided recommendations to follow when undertaking and interpreting anthropometrical assessments in individuals with a motor disability. Prior to undertaking any assessment, practitioners and researchers are encouraged to first consider the purpose and validity of what they wish to measure in each individual, as they present with their own unique characteristics. Most importantly, the safety and dignity of each individual must be respected. Anthropometrical assessment, through measures of body mass, stature, sitting height, arm span, skinfolds, girths, lengths and breadths, provides a systematic approach to understanding the variations in human body size, shape, proportion and composition, with anthropometry assuming a crucial role in several fields, including anthropology, ergonomics, nutrition, medicine, and exercise science. The International Standards for Anthropometric Assessment (International Society for the Advancement of Kinanthropometry, ISAK) have been developed and refined over a period of over 30 years in order to guide the landmarking and measurement of a wide range of surface anthropometrical variables in able-bodied individuals in order for such measures to be reliable, repeatable and valid. However, there is currently a lack of consistency in the processes used when undertaking anthropometrical assessments in individuals with a motor disability. Motor disability refers to a broad spectrum of physical impairments that affect an individual's ability to control voluntary movements of the body. These impairments may result from congenital conditions, injuries, or diseases that affect the nervous system, muscles, or bones. Motor disabilities can range in severity from mild limitations in coordination and balance to complete paralysis, and they may impact mobility, dexterity, and the ability to perform everyday tasks independently. Currently, the ISAK protocol does not guide adaptations for landmarking, measurement or interpretation in this population. Therefore, the ISAK working group on motor disability has reviewed the literature and provided recommendations to follow when undertaking and interpreting anthropometrical assessments in individuals with a motor disability. Since individuals with the same diagnosis may present with very different functional capabilities, there cannot be one single modification to the ISAK protocol that applies to all individuals with a motor disability. Therefore, the recommendations provided in this manuscript are detailed specifically for each individual measure, including commentary around the process of landmarking, with examples of modifications to be made in relation to a variety of impairment presentations. Recommendations are also provided regarding equipment required, communication with the individual being measured, and what information should be included in the informed consent that would precede any anthropometrical assessment. Practitioners are also encouraged to carefully consider the purpose behind the assessment they're undertaking and whether all measures are actually required. For example, the use of descriptive health indices such as waist to hip ratio or body mass index may not be valid in many individuals with a motor disability, which may negate the need to stature height or body mass. The adaptations to the ISAK Manual proposed here will make it possible for all professionals and researchers working in this field to compare the results of their assessments and to confidently determine changes in measures over time. However, it is essential to understand each subject as an individual case. The selection of anthropometric measurements when profiling an individual with a motor disability must be done carefully, taking into account: (a) the practical usefulness of each measurement in relation to the objective of the study or assessment and (b) the measurement error that may be present in relation to the physical and functional characteristics of each subject. The anthropometrist must always explain the assessment procedures inherent to each measurement before it is taken, be attentive to any signs of discomfort that may exist on the part of the subject, and respect the dignity of each participant. Most importantly, the safety, comfort, and dignity of each individual must be respected.